The value of clinical staging of thyroid cancer using ultrasonography and CT scan and its correlation with intraoperative and histopathological findings - Chandra, Mahesh; Kundu, Reetu; Kochhar, Suman (International Surgery Journal, 2019)
Background: Thyroid cancer has incidence of 4 patients per 100,000 populations per year and majority are present between 25-65 years age. Over the years, various imaging have been utilised to detect thyroid cancer but its TNM-staging remains pathological only made on the resected specimen. The aims and objectives of the study was to differentiate thyroid cancer from others lesions, clinically stage them on ultrasonography and CT scan and correlate with histological findings. Methods: This prospective study was done from March 2012 to April 2015. A total of forty patients of FNAC proven or highly suspicious of thyroid cancer underwent ultrasonography (USG) and CT scan TNM staging before planned surgery. The histopathogical findings of resected specimen were correlated with clinical TNM staging of thyroid cancer. The significance of difference between USG and CT scan was calculated using Chi-square test. The difference in the sensitivity as well in specificity was statistically highly significant (p<0.001) and significant (p<0.005), respectively. Results: The largest number of thyroid cancer patient was between 31-40 years with male: female ratio of 1: 4 and 60% presented as asymptomatic lump in the neck. Out of two imaging, the CT scan had more sensitivity and specificity in thyroid cancer staging compared to ultrasonography which had 87.5% sensitivity and 95.8% specificity, respectively. Conclusions: Overall, the CT scan has more sensitivity and specificity in the assessment of thyroid lesions, thus it may be recommended as imaging method of choice in the clinical staging of thyroid cancer either alone in combination of ultrasonography.